Snow in the Russian Language Picture of the World - Kazimianec, Jelena (Respectus Philologicus, 2013)
This article carries out a semantic and pragmatic description of the Russian word снег “snow,” considering its synonymic and word-formation relations, establishing a family of words, and defining the semantic oppositions in which the word “snow” and its separate word usages appear. The author pays particular attention to the pragmatic connotations of this word, placing them against a background of the different foreign language connotations of appropriating words. The article further investigates the group of the words designating the weather phenomena that typically accompany snowfall: метель “a snowstorm,” вьюга “a snowstorm, a blizzard,” буран “a severe snowstorm,” and пурга “a snowstorm, a blizzard,” defining their semantic range and features of how they function in speech. On the basis of an analysis of the facts provided in dictionaries and poetic discourses, the author comes to a conclusion about the existence of a separate semantic group of words with this meaning that proves the special importance of this weather phenomenon for Russians. The analysis also provides a way to determine that, unlike in other languages, the concept of “snow” in the Russian picture of the world is considered as an active figure: the word combination снег идет “it is snowing” is associated with positive concepts about happiness, the novelty of life, satisfaction with Russian aesthetic concepts about beauty, etc. The author proves that words and concepts united by the component “snow” possess a certain romantic nuance in which, it may be claimed, the unique character of Russian culture consists.
Keywords: Concept; Language Picture of the World; Semantic Oppositions; Conceptualization of the World; Poetic Discourse